Nexus of Fisheries and Agriculture Production and Urbanization on Ecological Footprint: New Evidence from Indonesian Economy - Abdunnur, Abdunnur (International Journal of Energy Economics and Policy, 2020)
The current examination is motivated to identify the link between fisheries, agriculture, urbanization, and the environment. In doing so, the present study is motivated to examine the Indonesian economy due to its massive population, marine-centered location, and almost equal rural-urban ratio. Hence, the current examination analyzed the influence of fisheries production, Agriculture production, and Urban development on the ecological footprint in Indonesia. The novelty of the present study lies in being the pioneer examination to study the joint effect of the mentioned variables on ecological footprint. We applied a novel methodology of ARDL bound testing cointegration to confirm the long and short run connection between fisheries, agriculture, urban development, and ecological footprint in Indonesia. The results of ARDL confirm that urban development, agriculture, and fisheries production has a positive and significant impact on the ecological footprint in the long-run. However, only a negative impact is found from agriculture production to ecological footprint in the short-run period in Indonesia. The present study recommended that the Indonesian government need to introduce some technology-oriented production system for fisheries and agriculture sector in order to reduce the ecological footprint in the Indonesian Economy. Keywords: Fisheries production, urban development, ecological footprint, Indonesia. JEL Classifications: Q22, Q57, R51 DOI: https://doi.org/10.32479/ijeep.9172